Assessing Unconfined Vapor Cloud Explosions (Uvce) Physical Effects: A Software Built For Modelling With Bst Methodology - Tahsin Aykan Kepekli (Gazi Üniversitesi Fen Bilimleri Dergisi)
The calculation of physical effects of unconfined vapour cloud explosions (UVCE), which are caused by explosive atmosphere, is important for risk assessment studies. During the evaluation of explosive atmospheres, effects of a possible explosion are determined in order to take safety measures. There are various algorithms for calculating the overpressure. In physical effect calculations, evaluation of the surrounding environment and chemical reaction are important criteria for accuracy of the results. Usually, a large portion of risk assessment studies neglect overpressure damage assessment as these algorithms cannot be understood or implemented easily due to difficulties in usage. There are various software used in calculating explosion overpressure, however these software generally are run without assessing operating limits and scenario parameters correctly. Thereby, explosion effects cannot be evaluated properly in many explosive atmosphere risk assessments. Taking this as the basis for our aim, an overpressure calculation software called ExCALc has been coded for use in UVCE risk assessment studies. ExCALc uses Baker-Strehlow-Tang (BST) model. The parameters are input in a user friendly way and the scenario results are calculated for varying distances. It is thought that for complex methodology used in assessments, simplifying tools will benefit industrial safety in the long term.